Quantifying the surface heat transfer on transpiration cooled porous materials in laminar and turbulent hypersonic boundary layers - Naved, I; Hermann, T; Hambidge, C; Ifti, HS; McGilvray, M; Tirichenko, IS; Vandeperre, L (ESA Conference Bureau / ATPI Corporate Events, 2022)
The design of a transpiration cooled system requires detailed local heat transfer information on and in the vicinity of the porous injector; however, limited spatially resolved experimental studies exist, particularly in hypersonic flows. In this work experiments were conducted on a flat plate model in the Oxford High Density Tunnel at Mach 6.1 in both laminar and turbulent regimes. Spatially resolved 2D surface heat transfer measurements were acquired by imaging directly on and downstream of two micro-porous transpiration cooled injectors (METAPOR CE170 and Zirconia) using high-speed infra-thermography. Whilst injection in the laminar regime results in a steady, monotonic reduction in heat transfer from the start of the injector, a flatter profile is present for the turbulent cases where turbulent mixing inhibits surface heat transfer reduction. It was found that a modification to existing relations from film theory successfully correlates the stream-wise heat transfer distribution on the injector for different blowing rates of Nitrogen and Helium injection. A key result is that Helium performs much better than reported in previous experiments for a turbulent boundary layer.